Amor (or, the Bat who thought she was an owl) - Tobias, Mary Ann Manalang (Quezon City, Philippines : Aklat Adarna, 1999)
Her father is an owl. Her mother is an owl. Is there any reason to think she ISN'T an owl?
Keywords: Bats--Fiction; Orphans--Fiction